HIV-1 Nef promotes migration and chemokine synthesis of human basophils and mast cells through the interaction with CXCR4. Issue 1 (December 2016) - Rossi, Francesca; Prevete, Nella; Rivellese, Felice; Lobasso, Antonio; Napolitano, Filomena; Granata, Francescopaolo; Selleri, Carmine; Paulis, Amato
Abstract Background The Nef protein can be detected in plasma of HIV-1-infected patients and plays a role in the pathogenesis of HIV-1. Nef produced during the early stages of infection is fundamental in creating the ideal environment for viral replication, e.g. by reducing the ability of infected cells to induce an immune response. Aim Based on previous experience showing that both Tat and gp41 of HIV-1 are potent chemotactic factors for basophils and mast cells, and gp120 is a powerful stimulus for the release of histamine and cytokines (IL-4 and IL-13) from basophils, in this study we aimed to verify if the HIV Nef protein can exert some effects on basophils and mast cells purified from healthy volunteers through the interaction with the CXCL12 receptor, CXCR4. Methods Basophils purified from peripheral blood cells of 30 healthy volunteers and mast cells obtained from lung tissue of ten healthy volunteers were tested by flow cytometric analysis, chemotaxis and chemokine production by ELISA assays. Results Nef is a potent chemoattractant for basophils and lung mast cells obtained from healthy, HIV-1 and HIV-2 seronegative individuals. Incubation of basophils and mast cells with Nef induces the release of chemokines (CXCL8/IL-8 and CCL3/MIP-1α). The chemotactic activity of Nef on basophils and mast cells is mediated by the interaction with CXCR4 receptors, being blocked by preincubation of FcεRI+ cells with an anti-CXCR4 Ab. Stimulation with Nef or CXCL12/SDF-1α, a CXCR4 ligand, desensitizes basophils to a subsequent challenge with an autologous or heterologous stimulus. Conclusions These results indicate that Nef, a HIV-1-encoded α-chemokine homolog protein, plays a direct role in basophils and mast cell recruitment and activation at sites of HIV-1 replication, by promoting directional migration of human FcεRI+ cells and the release of chemokines from these cells. Together with our previous results, these data suggest that FcεRI+ cells contribute to the dysregulation of the immune system in HIV-1 infection.